2010
DOI: 10.1074/jbc.m109.062265
|View full text |Cite
|
Sign up to set email alerts
|

Derepression of HMGA2 via Removal of ZBRK1/BRCA1/CtIP Complex Enhances Mammary Tumorigenesis

Abstract: The high mobility group AT-hook 2 (HMGA2), a DNA architectural protein, is highly regulated during development and plays an important role in tumorigenesis. Indeed, HMGA2 was overexpressed in many different kinds of tumors. However, the mechanisms regulating HMGA2 expression remain elusive. Using microarray analysis, we found that HMGA2, along with a dozen of other genes, was co-repressed by ZBRK1, BRCA1, and CtIP. BRCA1 exerts its transcriptional repression activity through interaction with the transcriptiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
47
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 42 publications
(49 reference statements)
1
47
0
Order By: Relevance
“…A group of genes have been identified to be tentatively regulated by ZBRK1 (25). Among these, GADD45A, Angiopoietin 1, and high mobility group AT-hook 2 have been shown to be regulated by ZBRK1 through interaction with the BRCA1⅐CtIP complex (27,28,32). In addition, our preliminary results showed that constitutive exogenous expression of ZBRK1 had no effect on the activation of cell cycle arrest and apoptosis in HeLa and U2OS cells, suggesting that transcriptional activation of genes essential for growth arrest or cell death are dependent on ZBRK1 repression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A group of genes have been identified to be tentatively regulated by ZBRK1 (25). Among these, GADD45A, Angiopoietin 1, and high mobility group AT-hook 2 have been shown to be regulated by ZBRK1 through interaction with the BRCA1⅐CtIP complex (27,28,32). In addition, our preliminary results showed that constitutive exogenous expression of ZBRK1 had no effect on the activation of cell cycle arrest and apoptosis in HeLa and U2OS cells, suggesting that transcriptional activation of genes essential for growth arrest or cell death are dependent on ZBRK1 repression.…”
Section: Discussionmentioning
confidence: 99%
“…ZBRK1 thus represents the first KRAP zinc finger protein (KRAB-ZFP) harboring two independent repression domains. ZBRK1 association with BRCA1 and CtIP repress transcription of Angiopoietin 1 (27) and high mobility group AT-hook 2 (28). The same repressor complex can also regulate the DNA damage response gene GADD45A for the maintenance of genomic integrity (29 -31).…”
mentioning
confidence: 99%
“…We found that MIR182 repression of BRCA1 expression will release a negative regulation and result in HMGA2 overexpression. 11,25 We propose that MIR182 overexpression in high-grade serous ovarian carcinoma may be in part or completely responsible for HMGA2 overexpression. Although MIR182 and HMGA2 overexpression are found in nearly 70% of high-grade serous ovarian carcinoma (this study and Mahajan et al 16 and Wei et al 17 ), low correlation of expression of these two genes was found (r ¼ 0.23) in this study.…”
Section: Discussionmentioning
confidence: 96%
“…16,17 The major tumorigenic functions of HMGA2 in the pathogenesis of high-grade serous ovarian carcinoma likely include regulation of epithelial mesenchymal transition. 24 A study by Ahmed et al 25 shows that BRCA1, ZBRK1 and CtIP form a repression complex that coordinately inhibits HMGA2 expression via a ZBRK1 recognition site in the HMGA2 promoter. We found that MIR182 repression of BRCA1 expression will release a negative regulation and result in HMGA2 overexpression.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that HMGA2 binds the complex formed by pRB and HDAC1 to dissociate pRB from genomic promoter regions and promotes the transcriptional activity of E2F1 and blocks the G1/S transition to inhibit the cell proliferation (22). It has been discovered that HMGA2 is upregulated in many benign and malignant tumors, such as colorectal, breast, pancreatic, ovarian, and lung cancer (25)(26)(27)(28). In the present study, it was found that the mRNA and protein levels of HMGA2 were often upregulated in GBC tissues.…”
Section: Discussionmentioning
confidence: 99%